위장관 간질 종양에서 c-kit 유전자 변이 - 박종경(Jong Kyung Park); 이채영(Chae Young Lee); 김진조(Jin Jo Kim); 진형민(Hyung Min Chin); 김욱(Wook Kim); 박조현(Cho Hyun Park); 전해명(Hae Myung Jeon); 박승만(Seung Man Park); 임근우(Keun Woo Lim); 박우배(Woo Bae Park); 김승남(Seung Nam Kim); 김인철(In Chul Kim); et al. (Annals of surgical treatment and research, 2004)
Purpose: Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumor, and express the KIT protein. Previous studies have reported KIT phosphorylation to be the principal biological event in the tumoriogenesis of GIST, which is generally evoked by the conformational mutation of KIT receptors. The aim of this study was to evaluate the frequency and category of c-kit mutations and their prognostic relevance. Methods: The frequency and category of the c-kit mutations and the correlation between clinical outcome and the c-kit mutations were analyzed and the significance of the c-kit mutations examined as independent prognostic factors in 84 cases of GIST. The c-kit mutations were measured by polymerase chain reaction and DNA sequencing, using an ABI 3700 sequencer. Results: c-kit mutations were noted in 14 of the 84 cases (16.7%) of GIST. Mutations in exon 11 were found in 11 cases (78.6%), exon 9 in 2 (14.3%) and exon 13 in 1 (7.1%), but no mutation was noted in exon 17. Of the mutations in exon 11, missense mutations were observed in 9 cases and frameshift mutations in 2. Among the 14 cases with c-kit mutations, 1 (7.1%) was found in a very low risk patient, 4 (28.6%) in intermediate risk patients and 9 (64.3%) in high risk patients. The c-kit mutations were observed more frequently in high risk patients (P=0.0366). However, there was no significant difference between the c-kit mutations and the survival rate. Conclusion: These results suggest that kit mutations might have a pathogenetic role in GIST, 550∼560 in exon 11 of c-kit gene is the conserving area of mutation and c-kit mutations are uncertain as prognostic factors in GIST. However, further study will be required. KCI Citation Count: 0